A new species of the genus Leucheria (Asteraceae, Nassauvieae) from Argentina - Jara-Arancio, Paola; Ratto, Francisco; Bartoli, Adriana; Arancio, Gina; Carmona-Ortiz, Martín R. (Phytotaxa, 2019)
Leucheria arancioi Jara-Arancio, Ratto & Adr. Bartoli (Asteraceae, Nassauvieae) is recognized as a new species. It was previously known as L. diemii var. purpurea Ratto, Bello & Adr. Bartoli. This is a perennial herb that inhabits the western part of the province of Santa Cruz, Department Río Chico, in the Patagonian phytogeographic province. Evaluation of morphological and molecular differences between the varieties of L. diemii showed that there are discriminating characters that warrant recognition of L. arancioi as a new species.